Die südeuropäischen Arten der Gattung Echinodera Wollaston und die Gattung Ruteria Roudier stat. n. (Coleoptera: Curculionidae: Cryptorhynchinae). - Stüben, Peter E. (Contributions to Entomology = Beiträge zur Entomologie, 1998)
The species of Echinodera Wollaston, 1864 of southern Europe are revised. Ruteria Roudier, 1954 stat. n., previously treated as a subgenus of Echinodera, is attributed generic status. Dieckmannia subg. n. (type species: Acalles brisouti Reitter, 1885) of the genus Echinodera and the following 6 species and subspecies are described: Echinodera romanboroveci sp. n. [Montenegro], E. behnei sp. n. [Makedonia], E. pseudovariegata sp. n. [Crete, Rhodes], E. ingowolfi sp. n. [Greece: Astakós], E. roudieri sp. n. [Spain: Alicante], E. brisouti peneckei ssp. n. [Dalmatia]. Nine species are redescribed: Echinodera variegata (Boheman, 1837), E. horridula (Reitter, 1888), E. major (A. & F. Solari, 1907), E. capiomonti (Brisout, 1864), E. brisouti (Reitter, 1885), E. valida (Hampe, 1864), E. peragalloi (Chevrolat, 1863), E. merkli (Meyer, 1896), E. ochsi (F. Solari, 1952). Lectotypes are designated for Acalles horridula Reitter, 1888, Acalles brisouti Reitter, 1885 und Acalles merkli Meyer, 1896. Relevant external characters and the male genitalia of the revised taxa are illustrated. Diagnostic keys allowing separation of genera (Acalles, Dichromacalles, Ruteria and Echinodera) and identification of the subgenera and species of Echinodera are presented.KeywordsSouth Europe, taxonomy, Curculionidae, Cryptorhynchinae, Echinodera, Ruteria, new subgenera, new species, designation of lectotypes, identification key.Nomenclatural ActsRuteria Roudier, 1954 (Curculionidae), stat. rev. hitherto a subgenus of Echinodera Wollaston, 1864Dieckmannia Stüben, 1998 (Echinodera), sgen. n.brisouti (Reitter, 1885) (Echinodera (Dieckmannia)), Lectotype described as Acalles brisoutimerkli (Meyer, 1896) (Echinodera (Dieckmannia)), Lectotype described as Acalles merkliroudieri Stüben, 1998 (Echinodera (Dieckmannia)), spec. n.peneckei Stüben, 1998 (Echinodera (Dieckmannia) brisouti), sspec. n.behnei Stüben, 1998 (Echinodera (Echinodera)), spec. n.horridula (Reitter, 1888) (Echinodera (Echinodera)), Lectotype described as Acalles horridulusingowolfi Stüben, 1998 (Echinodera (Echinodera)), spec. n.pseudovariegata Stüben, 1998 (Echinodera (Echinodera)), spec. n.romanboroveci Stüben, 1998 (Echinodera (Echinodera)), spec. n.anatolica (Caldara, 1978) (Ruteria), comb. n. hitherto Echinodera (?) anatolicabellieri (Reiche, 1860) (Ruteria), comb. n. hitherto Acalles bellierigraeca (Caldara, 1973) (Ruteria), comb. n. hitherto Echinodera (?) graecahypocrita (Bohemann, 1837) (Ruteria), comb. n. hitherto Acalles hipocritusnormandi (A. & F. Solari, 1907) (Ruteria), comb. n. hitherto Echinodera(?) normandipaganettii (Solari, 1952) (Ruteria), comb. n. hitherto Echinodera (?) paganettiipelionis (Frieser, 1955) (Ruteria), comb. n. hitherto Echinodera (?) pelionisporcheti (Hoffmann, 1935) (Ruteria), comb. n. hitherto Echinodera (?) porchetityrrhenica (Caldara, 1978) (Ruteria), comb. n. hitherto Echinodera (?) tyrrhenica